2019
DOI: 10.1055/a-0806-8986
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral femoral capital physeal fractures in an adult cat with suspected congenital primary hypothyroidism

Abstract: A 4-year-old, neutered male European shorthair was presented for evaluation of right hind limb lameness. Radiographs revealed bilateral femoral capital physeal fractures, widened vertebral growth plates and constipation. Physical findings included lethargy, mental dullness, mild hypothermia, retarded growth, pharyngeal stridor, moderate muscle atrophy of pelvic limbs, hair coat abnormalities, and lack of defecat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Recent studies revealed that 1 out of 2000 babies is born with CH 15. In dogs and cats, this condition is rare with only a few cases reported for each species 4 5 13 14 16–28. When a young dog or cat is presented with lethargy, disproportionate dwarfism and a juvenile hair coat, CH should always be considered in the differential diagnosis 29.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that 1 out of 2000 babies is born with CH 15. In dogs and cats, this condition is rare with only a few cases reported for each species 4 5 13 14 16–28. When a young dog or cat is presented with lethargy, disproportionate dwarfism and a juvenile hair coat, CH should always be considered in the differential diagnosis 29.…”
Section: Discussionmentioning
confidence: 99%
“…These typically occur secondarily to physeal dysplasia and metaphyseal disorders, with a higher incidence in overweight, male, neutered cats and in certain breeds of pedigree cat. 30,[35][36][37][38][39][40][41][42] They can usually be identified by the lack of a history of trauma, often progressive clinical signs, a potential for bilateral lesions and signalment. Two pathological entities are described.…”
Section: Proximal Physeal Fractures and Femoral Neck Fracturesmentioning
confidence: 99%
“…Despite this, there is a lack of information related to non-traumatic "acetabular physeal fractures" (APFs). The acetabular physis closes between 20 and 24 weeks of age [1], and it is unknown whether APFs share an etiological link with "Feline Epiphyseal Dysplasia Syndrome", where spontaneous fractures of the femoral head are described [5][6][7][8] in male patients, typically early-neutered, young, obese [8], and/or hypothyroid [9]. There are no data in the literature supporting a similar theory for the origin of APF.…”
Section: Introductionmentioning
confidence: 99%